Correlation between Serum Endocan and HbA1c in Type 1 Diabetes Mellitus Patients - Catur Suci Sutrisnani; Sidarti Soehita Satjadibrata; Soebagijo Poegoeh Edijanto; Anik Widijanti; Haryudi Aji Cahyono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Endothelial dysfunction is a key mechanism in the pathogenesis of complications of cardiovascular disease in Diabetes Mellitus (DM) patients. One of the new biomarkers for inflammatory conditions and endothelial dysfunction is endocan. This study aimed to determine the correlation between endocan levels and HbA1c in type 1 DM patients. This study was an analytical observational study with a cross-sectional approach performed at the Dr. Saiful Anwar Hospital, Malang from May to August 2019. The research subjects were children aged 10-18 years with a diagnosis of type 1 DM who met the inclusion criteria. Students who underwent routine health checks participated as the control group. In both groups, serum endocan levels were measured using the ELISA method and HbA1c levels were measured by the HPLC method. Independent T-test analysis was used to determine the differences between both groups and the Pearson test was used to determine the correlation between serum endocan and HbA1c with SPSS version 23. In this study, there were 40 type 1 DM patients and 40 healthy controls with a mean age of 14.5 (3.16) years in the type 1 DM group and 14.7 (0.99) years in the healthy control group. There was a higher number of female subjects in both the type 1 DM group (57.5%) and the healthy control group (65%). The mean endocan level in the type 1 DM group was higher than the control group and was statistically significant with 1090.61 (150.84) pg/mL vs. 775.56 (8.91) pg/mL, p=0.000). The mean value for HbA1c levels in the type 1 DM group was also significantly higher compared to the control group 9.63 (2.22%) vs. 4.69 (0.251%), p <0.001), respectively. There was a significant positive correlation between endocan levels and HbA1c in DM patients (p=0.025, r=0.354). This study showed a correlation between serum endocan levels and HbA1c in patients with type 1 DM.